Sedentary Profile of Adolescents Aged 12-15 Years at Pangudi Luhur Junior High School in Salatiga - Pulungan, Priska Lydia Sulistyawati; Messakh, Sanfia Tesabela; Triprasojo, Daniel (Indonesian Journal of Sport Management, 2024)
The technology designed to assist human life has undergone rapid development, but on the flip side, it has led to the emergence of a sedentary lifestyle (lack of physical activity). Sedentary behaviour is prevalent among teenagers who prefer playing with gadgets, lying down, and watching television. Engaging in sedentary behaviour for more than 5 hours a day can result in various dangerous health issues, including obesity. Therefore, teenagers must increase physical activities that support their overall health. A study was conducted to explore the passive profile of students aged 12-15 years at Pangudi Luhur Junior High School in Salatiga. The research employed a quantitative method with simple random sampling. The total population of the study was 223, and the sample size obtained using the Slovin formula was 143 students. Data were collected by completing the Adolescent Sedentary Questionnaire (ASAQ) by 150 students at SMP Pangudi Luhur Salatiga. The research findings indicate that many students engage in Sunday activities, totalling 988 minutes (16 hours and 28 minutes). Additionally, during the week, students spend 1054 minutes (17 hours and 34 minutes) on activities such as watching YouTube and DVDs.